In vitro effects of bmp-2, bmp-7, and bmp-13 on proliferation and differentation of mouse mesenchymal stem cells - Dorman, Lisa J; Tucci, Michelle; Benghuzzi, Hamed (Biomedical sciences instrumentation, 2012)
Mesenchymal stem cells (MSCs) have the capabilities to proliferate and differentiate into osteoblastic and chondrogenic lineages when stimulated with bone morphogenic proteins (BMPs). BMPs play a vital role in skeletal development. BMPs bind to their cell surface receptors on MSCs and send signals to the cell nucleus which results to the synthesis of macromolecules involved in cartilage and bone formation and then the mesenchymal cell differentiates into chondrocytes or osteoblasts. The objective of this study was to evaluate the effects of BMP-2, BMP-7, and BMP-13 on undifferentiated MSCs for cellular damage markers, alkaline phosphatase, and morphological changes at 24, 72, 120, and 168 hours of culture. MSC viability, proliferation, cellular damage, and cellular morphology were evaluated after each time point. As early as 48 hours MSCs treated with BMPs resulted in morphological changes, and increased cell numbers. At 120 and 168 hours BMP-13 resulted in morphological changes resembling chrondrocytes. It was concluded that BMPs have no adverse effects on proliferation and are non- toxic to undiffetentiated MSCs.